Pharmacokinetic parameters of Amoxicillin in Bangladeshi volunteers: a preliminary evaluation (Bangladesh Journal of Physiology and Pharmacology, 2014)
The present study was designed to get preliminary idea about the pharmacokinetic behavior of the Bangladeshi population through estimating plasma amoxicillin concentration by High-Performance Liquid Chromatography (HPLC) with ultraviolet detection. In this study, Bangladeshi healthy volunteers were divided in two groups, 8 Bangladeshi Bangalee and 7 Bangladeshi Tribal male healthy volunteers. Both the groups received 500 mg of amoxicillin in oral route and blood samples were collected at 0, 30, 60, 120, 180, 360 and 480 minutes after drug administration. After 1 week of washout period, same volunteers of two groups received 500 mg of amoxicillin in intravenous route. In case of oral route, the Cmax, AUC08h, Tmax and T1/2 values for Bangladeshi Bangalee and Tribal healthy volunteers were 6.78 ± 1.20 & 9.10 ± 1.34 ìg/mL, 1290.13 ± 158.39 & 1766.06 ± 188.37 ìg min/mL, 82.50 ± 32.05 & 102.86 ± 29.28 min and 96.05 ± 3.80 & 88.15 ± 5.33 min respectively. The difference in Cmax, AUC08h and T1/2 values between these two groups of volunteers was significant (p